2016
DOI: 10.1159/000455840
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Obesity

Abstract: Psoriasis is a common chronic inflammatory skin disease with a complex pathogenesis consisting of a genetic component, immune dysfunction, and environmental factors. It is associated with numerous comorbidities including psoriatic arthritis, cardiovascular disease, metabolic syndrome, and obesity. Evidence suggests that obesity is a risk factor for incident psoriasis, aggravates existing psoriasis, and that weight reduction may improve the severity of psoriasis in overweight individuals. Excess body weight may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
176
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(218 citation statements)
references
References 77 publications
6
176
1
10
Order By: Relevance
“…Individual PASI scores in this study ranged from 0.7 to 34.8 and the upper end of the PASI scale (up to 72) was not encountered. Over 75% of study patients were overweight with a high mean BMI of 29.6 kg/m 2 , which confirms epidemiological evidence . The inter‐ and intraobserver variability of image‐based PASI measurements in our study was low.…”
Section: Discussionsupporting
confidence: 85%
“…Individual PASI scores in this study ranged from 0.7 to 34.8 and the upper end of the PASI scale (up to 72) was not encountered. Over 75% of study patients were overweight with a high mean BMI of 29.6 kg/m 2 , which confirms epidemiological evidence . The inter‐ and intraobserver variability of image‐based PASI measurements in our study was low.…”
Section: Discussionsupporting
confidence: 85%
“…Accumulating evidence has indicated that psoriasis is clinically relevant to other systematic diseases, including Crohn's disease and obesity . The question that puzzles investigators regards the relationship and common features between psoriasis and those diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is frequently associated with metabolic syndrome including obesity . Overweight and weight gain have been shown to be predictive for the development of psoriasis .…”
Section: Introductionmentioning
confidence: 99%